2013
DOI: 10.1242/jcs.134262
|View full text |Cite
|
Sign up to set email alerts
|

Light-harvesting chlorophyll pigments enable mammalian mitochondria to capture photonic energy and produce ATP

Abstract: Sunlight is the most abundant energy source on this planet. However, the ability to convert sunlight into biological energy in the form of adenosine-59-triphosphate (ATP) is thought to be limited to chlorophyll-containing chloroplasts in photosynthetic organisms. Here we show that mammalian mitochondria can also capture light and synthesize ATP when mixed with a light-capturing metabolite of chlorophyll. The same metabolite fed to the worm Caenorhabditis elegans leads to increase in ATP synthesis upon light ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 103 publications
1
25
1
Order By: Relevance
“…One of the most surprising functions proposed for chlorophyll derivatives in mammals is the capacity to produce ATP [135]. Authors showed that upon incubation of isolated mice mitochondria and brain, heart and lens homogenates, homogenized duck fat, and alive Caenorhabditis elegans, with pyropheophytin a, the light exposure was able to increase ATP concentrations.…”
Section: Functions Of Chlorophylls At Animal Cell Levelmentioning
confidence: 99%
“…One of the most surprising functions proposed for chlorophyll derivatives in mammals is the capacity to produce ATP [135]. Authors showed that upon incubation of isolated mice mitochondria and brain, heart and lens homogenates, homogenized duck fat, and alive Caenorhabditis elegans, with pyropheophytin a, the light exposure was able to increase ATP concentrations.…”
Section: Functions Of Chlorophylls At Animal Cell Levelmentioning
confidence: 99%
“…In the subsequent experiment, ATP levels only increased in groups where P-a and NIR light were co-administered, and not in those in which P-a or NIR were given in isolation. This observation was further supported by in vivo demonstration in a Caenorhabditis elegans model that lifespan, respiration rate, and ATP levels increased significantly when both P-a and NIR were administered concomitantly (Xu et al, 2014). Given the multiplicity of these competing theories, it may be that NIR exerts its modulatory effects through several mechanisms instead of one.…”
Section: Cytochrome C 2+mentioning
confidence: 85%
“…This theory is supported by the fact that cellular ATP level increases are immediate after PBM stimulation (Quirk et al, 2016), suggesting that the intracellular changes mediating elevated ATP production are alterations in physical properties rather than chemical processes, as the latter tends to occur with a slight time lag (Sommer, 2019). Yet another group suggested that the photo-absorbent metabolite pyropheophorbide-a (P-a) of dietary chlorophyl could facilitate light-driven energy production processes in animals (Xu et al, 2014). Xu et al (2014) first examined whether P-a associates with the mitochondria after chlorophyl ingestion by looking at fluorescence emission levels of P-a from mammalian mitochondrial fragments.…”
Section: Cytochrome C 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent discoveries have shown the specific functions of several chlorophyll metabolites of developing in animal tissues, including the production of ATP, the regulation of the redox status in plasma, implications as visual pigments, and activation of specific nuclear receptors that could control lipid abnormalities in common diseases such as obesity, diabetes, and hyperlipidemia among others. Evidently, the origin of chlorophyll metabolites present in the animal body is circumscribed to the diet.…”
Section: Discussionmentioning
confidence: 99%